Frequency of Cholesteatoma in Chronic Suppurative Otitis Media and its Treatment Modality in a Tertiary Care Setup - A Retrospective Study (Medical Forum Monthly, 2022)
Objective: To explore the frequency of cholesteatoma in chronic suppurative otitis media and its treatment modality among Pakistani population.Study Design: Retrospective Observational StudyPlace and Duration of Study: This study was conducted at the department of otorhinolaryngology, Jinnah Post Graduate Medical Centre Karachi, Pakistan, from January 2015 to December 2020.Materials and Methods: All patients of CSOM were selected by using non probability purposive sampling technique. Data was collected from patients’ files. Patients with a history of severe systemic illness, those who were unfit for the surgery and those who refused were excluded. Structured proforma was used to collect information. Descriptive statistics were used to explore incidence of cholesteatoma in chronic suppurative otitis media.Results: We identified 677 patients through the coding system of our hospital between 1st of January 2015 till 31st of December 2020. Systemically ill patients, unfit patients for surgery and those who refused surgery were excluded. Females were in a higher number 373 (55.1%). The mean age was 21.74±8.97. For exploratory analysis, participants were divided into four age groups. Most common age group was between 6 to 20 years (52.4%). Out of 677 patients, 157 (23.1%) had cholesteatoma present.Conclusion: Cholesteatoma is known sequelae in CSOM patients. It needs extra care and expertise to prevent complications. Timely recognition and correct choice of management may result in better hearing outcomes. In addition, improvement in socioeconomic status (good hygiene) and awareness may reduce the number of cases.